INCREASE THE RELIABILITY OF CONTROL OF TECHNICAL STATE IS THERMODYNAMICALLY OBJECTS - Щапов, Павел Федорович; Осина, Татьяна Георгиевна (Eastern-European Journal of Enterprise Technologies, 2010)
The scientific challenge of obtaining additional information on the random measurement signals at the control of thermal conditions of the facility was considered. It is proved that the additional information are statistical variance decomposition of these signals.